Políticas educacionais e desenvolvimento: a experiência da Reserva Extrativista Marinha do Soure, Pará - FERREIRA, Lindomal dos Santos (2002)
Extractive reserves (RESEX) have emerged as important strategic alternative livelihoods. Integrated into the theoretical framework of sustainable development they have been presented in an empirical way as ample opportunities for co-existence between man and natural resources in sustainable relationships in order to harmonize the social, economic and ecological impacts of local populations. The aim of this study was to examine the role of education within the proposed development behind the proposal of extractive reserves, in particular the case of RESEX / Soure, verifying the viability of extractive reserves as a development model. The locus of the research was the Marine Extractive Reserve of Soure, Soure municipality, state of Pará was studied a population consisting of 278 families of "drawers of crab" / ACS Soure and 1475 fishermen associated with the Colony Fishing Soure 1/CP-Z- Zone 1. The research technique used was direct observation. And the research instruments used were the daily observation and semi-structured interviews. It was found that local natural resources are very rich, although most are threatened. It was also found that the most significant gathering activities in the areas of RESEX along with fishing is the tiração crab, since they are the guarantee of a more immediate financial income. It was observed that not only level of education of the interviewed population constitutes an obstacle to their development as well as their socio-cultural strategies are not being valued within the local government action, not in the plans of implementing the policy of creating this book CNPT / IBAMA. It was concluded that the absence of a socio-pedagogical process that correlates the social and cultural interests of the extractives is also a political aspect of creating the RESEX Soure but is yet to be conceived and organized with local residents and their organizations in Soure. It is actually talking about it. Anyway to put into question the true interests that move the action of the state and the people residing there.